2011
DOI: 10.1111/j.1742-7843.2011.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Remodelling of the Maternal Uterine Circulation during Pregnancy

Abstract: Sufficient uteroplacental blood flow is essential for normal pregnancy outcome and is accomplished by the coordinated growth and remodelling of the entire maternal uterine vasculature. The main focus of this MiniReview is to provide information on upstream (pre-placental) maternal uterine vascular remodelling that facilitates gestational increases in uterine blood flow. Consideration of the three-dimensional pattern of remodelling (circumferential enlargement versus axial elongation), changes in vessel biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 52 publications
4
68
0
Order By: Relevance
“…A previous report in the TgA model indicated that contraction to PE was increased compared with SD UA at late gestation (32). Our observation of a similar contraction to PE in intact arteries of SD and TgA UA indicates that this difference appears later in gestation, consistent with the increased sensitivity to ␣-adrenergic stimulation in late pregnancy compared with arteries from nonpregnant animals (27), and may be related to the great degree of remodeling that this vascular bed endures during gestation (22). Contraction to PE was greatly affected by preincubation with indomethacin in TgA, lending further support to an increased role for prostanoids in the local vascular response in TgA UA at early gestation.…”
Section: Discussionsupporting
confidence: 84%
“…A previous report in the TgA model indicated that contraction to PE was increased compared with SD UA at late gestation (32). Our observation of a similar contraction to PE in intact arteries of SD and TgA UA indicates that this difference appears later in gestation, consistent with the increased sensitivity to ␣-adrenergic stimulation in late pregnancy compared with arteries from nonpregnant animals (27), and may be related to the great degree of remodeling that this vascular bed endures during gestation (22). Contraction to PE was greatly affected by preincubation with indomethacin in TgA, lending further support to an increased role for prostanoids in the local vascular response in TgA UA at early gestation.…”
Section: Discussionsupporting
confidence: 84%
“…9 In aged dams, maximal constriction of the uterine artery to the α-adrenoceptor agonist phenylephrine was reduced by 21% ( Figure 2A and 2B), albeit sensitivity to phenylephrine was not altered (pEC 50 ; young: 7.5±0.1 versus aged: 7.3±0.1; P=0.12). Maximal constriction to high KCl buffer was reduced by 35% in aged compared with young dams at gestational day 20 (P<0.05; Figure 2C).…”
Section: Uterine Artery Functionmentioning
confidence: 91%
“…Dramatic maternal hemodynamic changes that occur during gestation include an increased blood volume, enhanced cardiac output, and reduced total peripheral resistance. 8 These maternal cardiovascular adaptations enable a progressive increase in blood supply to the placenta (via the uterine artery) 9 to support the increasing demands of the growing fetus throughout gestation. The mechanisms of reduced peripheral vascular resistance during normal pregnancy are not completely understood but include increased bioavailability of endothelial-derived vasodilators, such as nitric oxide (NO) and endothelial-derived hyperpolarization.…”
mentioning
confidence: 99%
“…The factors responsible for the remodeling of the uterine vasculature during pregnancy, particularly the main uterine artery, are influenced by a combination of local and systemic pregnancy-dependent factors [2,15]. Studies using pseudopregnant mice demonstrated that the conceptus is not involved in the initial remodeling response of the uterine artery [11], but as pregnancy progresses, the fetoplacental unit plays a major role in mediating expansion of the uteroplacental vasculature [16,17].…”
Section: Introductionmentioning
confidence: 98%